A Case Study of Consolidating Two Database A–Z Lists for Better Staff and User Experiences - Quinn, Todd (Library resources & technical services, 2020)
This case study describes the consolidation and migration of the University of New Mexico’s University Libraries’ database A-Z lists. A subject librarian lead the nine-month project that included most subject librarians, the electronic resources team, the Director of Collections, and the web & discovery librarian. The project also provided the UL the opportunity to review all the resources in the lists, and update all descriptions, and create new workflows for adding and managing a single list.